The Graphic Language of Ecological Packaging Designs - Karaalioğlu, Sevim (Universitas Komputer Indonesia, 2025)
In today's world, the influence of sustainability on the field of design is steadily increasing, and packaging design has emerged as one of the key areas where this awareness becomes visible. Packaging produced with recyclable, reusable, and environmentally friendly materials reflects brands’ sustainability approaches. The graphic language of ecological packaging plays a significant role in conveying its intended message. Various visual elements such as color, typography, and symbols strongly reflect environmental sensitivity in graphic expression. This design language not only positively contributes to the brand identity but also enhances the visibility of environmental awareness for the consumer. Therefore, sustainable packaging serves as a powerful communication tool, not only through its environmentally safe physical properties but also through its graphic language that supports ecological awareness. This study focuses on how graphic elements in packaging design convey messages of sustainability, and addresses the relationship between graphic expression, design, and nature. Selected examples of ecological packaging are examined through visual elements such as typography, color, texture, form, and material using a descriptive analysis method. Nature-inspired forms, organic lines, and indicators play a crucial role in communicating sustainability messages in packaging design. Especially, designs that emphasize a minimalist aesthetic are valuable in their contribution to raising environmental awareness among consumers. This study aims to reveal the impact of graphic expression in ecological packaging designs and to develop proposals that will contribute to the understanding of sustainable design. Keywords: Ecological Design, Sustainability, Packaging Design, Graphic Design, Visual Communication